Talent Management Practices, Competitive Strategy And Government Support Toward Export Performance Of Malaysian Food Processing Smes - Loganathan, Khamini (2019)
With the rise of global competition, organisations must acquire high talents and enhance their capabilities on response towards changing market requirements. This study employs talent-based theory and resource-based theory to formulate a new talent management practice-competitive strategy-performance theoretical model concerning firms operating in the export sectors. This thesis explores the effect of talent management practices (talent attraction, talent development and talent retention) on competitive strategy and export performance. This research also addresses moderating effect of government support between competitive strategy and export performance. This research explores the mediating role of competitive strategies in the relation between talent management practices and export performances. The research model is tested using the Partial Least Squared (PLS) technique. The empirical results have indicated that talent retention is significantly related to export performance and competitive strategy. With the mediating effect of competitive strategy, has shown a significant positive relationship between talent development and export performance. Government support is important to strengthen the food processing SMEs export performance, by helping to improve the firm’s competitive strategy. The government support performs by government agencies create a platform and provide sufficient source to expand competitive strategies.